Code-Mixing by Agnez Mo and Daniel Mananta in the Podcast Daniel Tetangga Kamu - Marcelino Albertus Sukamto; Samuel Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study examines code-mixing as used by Agnez Mo and Daniel Mananta in the podcast Daniel Tetangga Kamu (Your Neighbor Daniel), specifically in the episode Go International, Agnez Mo Selalu Bangga Mewakili Indonesia (Go International, Agnez Mo is Always Proud to Represent Indonesia). The analysis is based on Muysken’s (2000) theory of types of code-mixing. The research was conducted qualitatively, supported by simple quantitative calculations. The findings show that both speakers employed all three types of code-mixing. Moreover, congruent lexicalization, as the most complex type, was dominantly used by both, indicating strong language skills in both Agnez Mo and Daniel Mananta. However, Agnez Mo used code-mixing more frequently than Daniel Mananta in the video. This difference is more likely due to unequal speaking opportunities, as one served as the host and the other as the guest. Overall, this study provides useful findings and discussions on the significant patterns of code-mixing used in the podcast Daniel Tetangga Kamu (Your Neighbor Daniel). Future researchers are encouraged to explore code-mixing on newer digital platforms that are increasingly popular among youth, such as TikTok. Lastly, they are advised to complement Muysken’s (2000) structural framework with additional theories that examine social relationship or interactional functions.